Ações de cuidado nas relações intrageracionais em crianças em acolhimento institucional - Scipião, Ingryd Cintya Augusto Machado (2014)
According to the Statute of Children and Adolescents (1990) children and adolescents are conceived as subjects of rights, with absolute priority and development peculiar condition. Thus, if these rights were violated or threatened, will be applied protection measures. Within these measures, in that Statute, the foster institutional is proposed, with transitional and exceptional character. When the child goes out from family and community life, and she is upheld in an institution, the child is placed in a new development context, therefore, with new people, new places, and new relationships. According with Socio-Historical Psychology, theoretical support of this study, each context presents specific demands of socialization that influence child development and her subjectivity is constituted through the relations that the subject establishes in each context. These contexts bring challenges and proposals for the child and she needs to respond these. Then, whereas he is in relation to the other, in this moment, the subject is constituted, the interactions established during the foster institutional will be of paramount importance to the child. Among these interactions, we can cite situations involving aspects of moral development, specifically those that can ask (or not) the exercise of the virtues. About the intersection between these actions can then arise care actions beyond those involving the attending of an emerging need. The objective of this study is to investigate the presence of relation everyday permeated by care actions among children in foster institutional. For the scope of the objective three children were participated, with three years old and in foster care measure. The research is qualitative and the procedure for building the corpus was, mainly, the participant observation. Procedures with video and history in books were also used as supplementary procedures. The analysis of the corpus was made through Thematic Content Analysis, the episodes were grouped into analysis categories pre-and post-established. The preestablished were care actions related to body care, care actions related to socio affective aspects, and care actions related to body care and socio affective aspects simultaneously. The two post-established categories were dismemberment of the preceding categories, called care actions developed in child-child interaction, without the intervention of an adult, and care actions developed in child-child interaction, with direct intervention of the educator. The analysis indicated that in the everyday interaction between foster children, they identify the physical and emotional needs of each other foster member, and they are willing to help them in whatever way they can, emphasizing the importance of play and playful moments like mediators about these interactions. The care actions observed are based on children´s concepts and interpretations made from their experiences and largely refer to maternal care. The condition of being away from their family life can be an element that enables these actions. Finally, this study reaffirms the importance of designing the foster institution as a socialization and care space. It follows the importance of valuing and strengthening the positive aspects that arise in the relationships established by the children in this context, including the care actions, the research objective, which are components of the subjectivity of these children